Imaging Imageability: Behavioral Effects and Neural Correlates of Its Interaction with Affect and Context - Westbury, Chris F.; Cribben, Ivor; Cummine, Jacqueline (Frontiers in Human Neuroscience, 2016)
The construct of imageability refers to the extent to which a word evokes a tangible sensation. Previous research (Westbury, Shaoul, Hollis, Smithson, Briesemeister, Hofmann, & Jacobs, 2013) suggests that the behavioral effects attributed to a word’s imageability can be largely or wholly explained by two objective constructs, contextual density and estimated affect. Here, we extend these previous findings in two ways. First, we show that closely matched stimuli on the three measures of contextual density, estimated affect, and human-judged imageability show a three-way interaction in explaining variance in LD RTs, but that imagebility accounts for no additional variance after contextual density and estimated affect are entered first. Secondly, we demonstrate that the loci and functional connectivity (via graphical models) of the brain regions implicated in processing the three variables during that task are largely over-lapping and similar. These two lines of evidence support the conclusion that the effect usually attributed to human-judged imageability is largely or entirely due to the effects of other correlated measures that are directly computable.